PENINGKATAN KESEJAHTERAAN PENERIMA MANFAAT YAYASAN BAITUL MAAL (YBM) PLN PERSPEKTIF MAQASHID SYARIAH - Firly Intan Putih Ramadhan; Hascaryani, Tyas Danarti (Islamic Economics and finance in Focus, 2024)
This study aims to analyze the empowerment of gerobak cahaya which is one of the flagship programs of YBM PLN Malang City in distributing and utilizing zakat funds in the form of productive zakat, linked to aspects of maqashid sharia. The reason this research is important is because no previous research has been found with similar objects, so new findings are needed that can be used as material for further research. This research uses a qualitative research method with a case study approach based on interviews, observation and documentation. From this research it is known that YBM PLN Malang City has made efforts to help improve the welfare of the community, especially the beneficiaries of the YBM PLN Malang City gerobak cahaya through the implementation of empowering gerobak cahaya. The resulting welfare impact shows that the beneficiaries of the Malang City gerobak cahaya are not yet fully prosperous according to maqashid sharia, because one of the elements of maqashid sharia, namely reason (al-aql) is not fulfilled.